FACTORS ASSOCIATED WITH BEQUEST MOTIVES AMONG OLDER AMERICANS. (11th November 2018) - Dokos, M; Lee, Y; Liu, Y; Fauth, E
Abstract: It is important to understand to what extent older Americans have bequest motives because this has important ramifications regarding the impact of government policies on the macro-economy and on the extent to which wealth disparities are passed on from generation to generation. However, we know little about recent information on the trend of bequest motives in the U.S. and the factors influencing expectations to leave inheritances to children. Using data from the 2004 and 2014 Health and Retirement Study (HRS), we examined the strength of bequest motives and contributing demographic and economic factors among individuals aged 50 and above. The descriptive results show that the percentage of the samples indicating 100% certainty of leaving a bequest decreased from 20.3% in 2004 (n=14, 196) to 15.8% in 2014 (n=13, 654). The results of the Ordinary Least Squares (OLS) regression analyses indicate that the significant factors contributing to older Americans' probability of leaving an inheritance totaling 100, 000 or more remained relatively constant (e.g., higher net worth, higher household income, higher education, fewer children, being widowed, being male, being White, longer life expectancy, good/excellent perceived health, and younger age). This study concludes that bequest motives among older Americans were not strong (e.g., average probability was 38.8%, ranged 0–100%), and key contributing factors were similar from 2004–2014. Education about efficient ways to accumulate savings for the purpose of bequests would be beneficial for policy, to encourage financial independence of individuals and families via savings and wealth transfer, and to improve familial bonds through these transfers.